Implementas Al-Qur’an dalam Membentuk Akhlaq Al-Karimah di TPA Masjid Nurani Insani Gamol - M Umar Suparwoto (POTENSIA: Jurnal Kependidikan Islam, 2022)
In man there is a nature that must be maintained in the life of man. One of the human nature that must be maintained is morality or ethics. Because with these morals there is a difference between man and the other creatures of God's creation. Here the researcher wants to know how far the implementation of the Qur'an in forming al-kariman morals, to readers and their examiners, as mentioned in the interpretation of Surat Al-Baqarah verse 129. This research method is qualitative with a case study approach, which is one of descriptive research, with this study expected to reveal in depth about the morals of students at the Insani Gamol Mosque of Conscience landfill. Data collection techniques that are used in interviews, observations, and documentation. The results of this study showed that the morals of TPA Students of Masjid Nurani Insani Gamol have good morals even though they are not yet 100%. Hopefully by studying more diligently can achieve the quality of al-Karimah morals.